2017
DOI: 10.15407/spqeo20.04.406
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of transfer of electron excitation in a donor-acceptor system with a carbon chain and ways of its relaxation

Abstract: Abstract. The optical properties and dynamics of transport of electron excitation and the ways of its relaxation in the supramolecular D-π-A complex on the basis of merocyanines have been investigated. There have been found two components in the transfer of charge: fast and slow, which correspond to different conformational states of the carbon chain in merocyanines. It was found that the main photoluminescence of the studied molecular solutions of merocyanines by its nature is similar to the exciplex luminesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…But in Fig. 5 a, b it is shown that the PL depends on polarity even at 4.2 K [8].The common for both solvents is short-wave shift of the PL bands maxima at low temperature compared to bands maxima at room temperature.…”
Section: Optical Properties Of M-1 and M-2 Molecules In Toluenementioning
confidence: 83%
See 3 more Smart Citations
“…But in Fig. 5 a, b it is shown that the PL depends on polarity even at 4.2 K [8].The common for both solvents is short-wave shift of the PL bands maxima at low temperature compared to bands maxima at room temperature.…”
Section: Optical Properties Of M-1 and M-2 Molecules In Toluenementioning
confidence: 83%
“…The bands in PL spectra with 450 are caused by the electronic transitions from the local electronic states of dimethylamino group. The PL bands with 450 are necessitated by first singlet π electronic transition that strongly depends on a carbon chain conformation [8]. The absorption spectral bands with 498 and 545…”
Section: Optical Properties Of M-1 and M-2 Molecules In Acetonitrilementioning
confidence: 99%
See 2 more Smart Citations